Graffiti as a cultural scene in the cities: decoloniality and biopolitics / O grafite como cena cultural nas cidades: decolonialidade e biopolítica - Loures, Andrea de Freitas Rocha; Pilla, Maria Cecilia Barreto Amorim (Revista de Direito da Cidade, 2022)
Abstract Artistic manifestations afford our society the robustness to respond to potential human-rights violations, most notably freedom of speech in a hierarchical society governed by forms of power, which relate to the concept of biopolitics posited by Michael Foucault. It is believed that, within the scope of culture, art is restrained, governed and ranked by micro-powers that foment censorship, repression and restriction mechanisms, conceivably impeding democratic, constitutional accessibility to culture. Cultural control exerted by biopolitics on the society is perceptible in the expurgation of artistic manifestations, vitiation of the artist’s image and escalating detraction of art in the political and institutional scope. The relation between art and power in Brazil features a perpetuation of colonial matrix that permits micro-powers to dismantle cultural policies geared to diversity-based artistic manifestations. Based upon such premise, this paper aims to analyze to what extent graffiti can be considered a territory esthetical occupation and simultaneously a symbolic encroachment of not- available-to-everyone spaces. Keywords: Graffiti, Biopolitics, Descolonialism, Freedom of Speech.